2008
DOI: 10.1016/j.jss.2007.05.021
|View full text |Cite
|
Sign up to set email alerts
|

Postischemic Infusion of 17-β-Estradiol Protects Myocardial Function and Viability

Abstract: Background-Females demonstrate improved cardiac recovery after ischemia-reperfusion (I/R) injury compared to males. Attenuation of myocardial dysfunction with pre-ischemic estradiol suggests that estrogen may be an important mediator of this cardioprotection. However, it remains unclear whether post injury estradiol may have clinical potential in the treatment of acute myocardial infarction. We hypothesize that post-ischemic administration of 17β-estradiol will decrease myocardial I/R injury, and improve left … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 38 publications
(35 reference statements)
1
8
0
Order By: Relevance
“…Since LVEDP elevations are considered indexes of cardiac dysfunction, as observed in ischemia/ reperfusion [27], we speculate that the cardiodepression elicited by 17βE2 is not detrimental for the heart. This agrees with the cardioprotection elicited by nanomolar estrogen doses in male rats subject to ischemia/ reperfusion [28]. Also in women it has been reported by clinical studies that endogenous estrogens (as in premenopausal period) contribute to reduce the risk for cardiovascular events [29].…”
Section: Discussionsupporting
confidence: 88%
“…Since LVEDP elevations are considered indexes of cardiac dysfunction, as observed in ischemia/ reperfusion [27], we speculate that the cardiodepression elicited by 17βE2 is not detrimental for the heart. This agrees with the cardioprotection elicited by nanomolar estrogen doses in male rats subject to ischemia/ reperfusion [28]. Also in women it has been reported by clinical studies that endogenous estrogens (as in premenopausal period) contribute to reduce the risk for cardiovascular events [29].…”
Section: Discussionsupporting
confidence: 88%
“…Despite the protection afforded by administering the ER modulators before ischemia (preconditioning effect), a post-ischemic treatment approach (post-conditioning effect) with these ER-regulated pharmacological agents might be more clinically relevant. Recently, acute post-ischemic infusion with E2 has been found to improve left ventricular myocardial function after 25 min of ischemia (Terrell et al 2008). To further distinguish which ER activation mediates this post-conditioning effect, the post-ischemic infusion was replaced with PPT or DPN.…”
Section: Conclusion and Future Perspectivementioning
confidence: 99%
“…Administration of E2 attenuates cardiac dysfunction, suggesting that E2 may be involved in mediating this cardioprotection in females 4. Additionally, post-injury treatment with E2, demonstrates protection of myocardial function against I/R and may have clinical potential in the treatment of acute myocardial infarction 6. In this study, we further determined by what mechanisms E2 conveys this acute cardiac protection following I/R.…”
Section: Discussionmentioning
confidence: 88%
“…However, with respect to therapeutic potential in the treatment of acute myocardial infarction, post-insult administration of estrogen has more clinical appeal. Recently, our group demonstrated that post-ischemic infusion of 17β-estradiol (E2) throughout the 40 minute reperfusion period improved left ventricular (LV) function compared to control 6.…”
Section: Introductionmentioning
confidence: 99%